An examination of dispositional social needs, agent knowledge, and two dimensions of product anthropomorphism: A serial mediation model - Sohail, Sehar; Sajjad, Amber; Zafar, Sohail (Frontiers in Psychology, 2022)
Thriving attention has been paid to the process and concept of anthropomorphism in marketing literature, as the concept is considered to be a precursor of positive marketing outcomes. However, prior studies have not clarified the position or role of inductive reasoning and anthropomorphism or explained the relationship between anthropomorphism and consumer’s individual dispositions. This paper aims to delve into the relationship between consumer psychological and dispositional motivational traits for a given product advertisement that has been personified and imbued with human body features. Building on the literature, a conceptual model has been proposed in which the psychological process-agent knowledge and dispositional motivation to meet social needs has been taken as independent variables positively related to one another and also related individually the two distinct dimensions of anthropomorphism (i) physical anthropomorphism and (ii) anthropomorphic thinking. Further, it was empirically tested if these two dimensions and these independent variables are linked in a sequential manner. The results show that need for belonging is positively associated with the agent knowledge acquisition, physical anthropomorphism and anthropomorphic thinking for a given stimulus. Similarly, agent knowledge induced by a humanized stimulus was also positively associated with the two dimensions of anthropomorphism. Further, the two dimensions had positive relationship with one another. Finally, need for belonging also positively associated with agent knowledge and two dimensions of anthropomorphism in a sequential manner. Findings indicate that in order to induce anthropomorphic thinking because of which positive marketing outcomes takes place marketers need to take into account dispositional and psychological factors which might ultimately affect their anthropomorphic inferences.